Integrated Filtering Microstrip Duplex Antenna Array with High Isolation - Xian-Jing Lin; Ze-Ming Xie; Pei-Sheng Zhang (International Journal of Antennas and Propagation)
This paper presents a 2 × 1 integrated filtering microstrip duplex antenna array with high isolation and same polarization. The antenna consists of two radiating patches fed by two T-shaped probes and a power distributing duplex network (PDDN). The PDDN is composed of two bandstop filters and a 180-degree phase shift power divider. And the PDDN is designed to achieve the functions of power division, frequency selectivity, and port isolation. A Transmission Line (TL) model is adopted to design the PDDN, and the detailed synthesis procedure is presented. For demonstration, the proposed antenna is designed and fabricated. The implemented antenna achieves an average gain of 10 dBi, a cross-polarization ratio of 20 dB, and an isolation of 35 dB within the operation band.